Influence of SnO2 Content on the Humidity Dependent Impedance of the MgFe2O4-Fe2O3-SnO2 Compound - Maria Vesna Nikolic; Miloljub D. Lukovic (Chemosensors, 2020)
A porous MgFe2O4-Fe2O3-SnO2 bulk compound with varying SnO2 content was obtained by sintering an appropriate mixture of magnesium oxide, hematite and tin oxide nanopowders at 1000 and 1100 °C. The obtained structure was confirmed by X-ray diffraction analysis. Scanning electron microscopy was used to analyze sample morphology, showing that the addition of SnO2 resulted in an inhomogeneous microstructure with smaller grain size especially at 1000 °C. Significant grain growth of hematite grains was noted at 1100 °C. The influence of relative humidity in the range 30–90% was monitored at room temperature (25 °C) in the frequency range 42 Hz- 1 MHz. The highest reduction of impedance with humidity was noted at lower frequency. Addition of low amounts of SnO2 and sintering at 1000 °C resulted in the highest sensitivity at 105 Hz of 0.391 MΩ/%RH in the RH30–90% range, while the compound with the highest amount of SnO2 showed the largest decrease in impedance with increase in relative humidity ~26 times. All samples showed low hysteresis (below 2%). Complex impedance data was analyzed using equivalent circuits reflecting the dominant influence of the grain boundary in the lower relative humidity range (30–60%) and both grain boundary and grain components in the higher relative humidity range (60–90%).